2020
DOI: 10.1002/adma.202000769
|View full text |Cite
|
Sign up to set email alerts
|

Atomically Thin Hexagonal Boron Nitride and Its Heterostructures

Abstract: Atomically thin hexagonal boron nitride (h‐BN) is an emerging star of 2D materials. It is taken as an optimal substrate for other 2D‐material‐based devices owing to its atomical flatness, absence of dangling bonds, and excellent stability. Specifically, h‐BN is found to be a natural hyperbolic material in the mid‐infrared range, as well as a piezoelectric material. All the unique properties are beneficial for novel applications in optoelectronics and electronics. Currently, most of these applications are merel… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
67
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 99 publications
(76 citation statements)
references
References 233 publications
(362 reference statements)
1
67
0
Order By: Relevance
“…[ 25 ] Although some studies have shown that the 2D‐hBN‐based deep‐UV detector presents a high on/off ratio of 10 3 , the missing wave range (only less than 210 nm detectable) and low responsivity make it difficult for practical SBPD application. [ 26–30 ] Up to date, several 2D WBSs, such as GaS, [ 31,32 ] Ga 2 In 4 S 9 , [ 33 ] NiPS 3 , [ 34 ] FePS 3 , [ 35 ] and BiOBr, [ 36 ] own intrinsic large bandgap (up to 3.4 eV) showing poor wavelength selectivity in solar‐blind photodetection. Compared with these 2D WBSs, 2D ultrawide bandgap semiconductors (UWBSs), as the next generation of semiconductor materials with bandgaps significantly wider than the 3.4 eV, [ 5 ] are particularly suitable for solar‐blind photodetection.…”
Section: Introductionmentioning
confidence: 99%
“…[ 25 ] Although some studies have shown that the 2D‐hBN‐based deep‐UV detector presents a high on/off ratio of 10 3 , the missing wave range (only less than 210 nm detectable) and low responsivity make it difficult for practical SBPD application. [ 26–30 ] Up to date, several 2D WBSs, such as GaS, [ 31,32 ] Ga 2 In 4 S 9 , [ 33 ] NiPS 3 , [ 34 ] FePS 3 , [ 35 ] and BiOBr, [ 36 ] own intrinsic large bandgap (up to 3.4 eV) showing poor wavelength selectivity in solar‐blind photodetection. Compared with these 2D WBSs, 2D ultrawide bandgap semiconductors (UWBSs), as the next generation of semiconductor materials with bandgaps significantly wider than the 3.4 eV, [ 5 ] are particularly suitable for solar‐blind photodetection.…”
Section: Introductionmentioning
confidence: 99%
“…), [ 20,21 ] has attracted the widest attention, where their intrinsic bandgaps nearly cover the spectrum from infrared (IR) to ultraviolet. Simultaneously, some 2D materials, with large bandgap, such as hexagonal boron nitride (hBN) [ 22 ] and some transition metal oxides (α‐SbO 3 , etc. ), [ 23,24 ] also play a critical role in 2D materials‐based circuit applications.…”
Section: Introductionmentioning
confidence: 99%
“…[ 31 ] ferromagnetic materials. These thousand kinds of 2D materials, [ 11,32,33 ] including metals (such as graphene and metallic of metal chalcogenides), [ 34,35 ] semiconductors (such as MoS 2 , and black phosphorus [BP]), [ 3,18 ] and insulators (hBN and α‐SbO 3 ) [ 22,23,36,37 ] with different band structures, provide basic circuit building blocks for on‐chip photoelectric integration. [ 38 ] Moreover, dangling bond free surfaces of 2D materials also enable the flexible construction of vdW heterostructures through vdW integration, [ 39,40 ] providing promising material platforms for developing new devices with advanced functions.…”
Section: Introductionmentioning
confidence: 99%
“…[ 7–10 ] Recently, many 2D semiconductors such as 2D MoS 2 , [ 11 ] black phosphorene (BP), [ 12 ] InSe, [ 13–16 ] Bi 2 O 2 Se [ 17 ] have been intensively explored theoretically and experimentally. [ 18–24 ] However, 2D MoS 2 suffers from a low mobility (200 cm 2 V −1 s −1 ), resulting in a low on‐state current ( I on ), which cannot be applied to the high‐performance (HP) electronics. 2D Bi 2 O 2 Se transistors with a high electron mobility (29 000 cm 2 V −1 s −1 at 1.9 K) are appropriate for HP devices.…”
Section: Introductionmentioning
confidence: 99%